OBSERVATIONS ON SOME LIMNOLOGICAL ASPECTS OF FOUR IMPORTANT LAKES OF KUMAON HILLS OF U.P. AND SUGGESTIONS FOR THEIR PROPER EXPLOITATION - Johri, V K; Awasthi, S K; Sharma, S R; Tandon, N K; Joshi, L M (Indian Journal of Fisheries, 2011)
The paper, broadly aiming at eco-conservation, attempts to communicate certain limnological observationsin respect of four sprawling lakes viz. Nainital, Sattal, Bhimtal and Naukuchiatal of Kumaon hillsof U.P. on the basis of studies conducted during the year 1988. Values of relevant parameters exhibitingthe various physico-chemical properties of water of the aforesaid lakes have been incorporated anddiscussed. An account of planktonic population and occurrence of benthic organisms in the collectedsamples have also been depicted. Control of Nainitallake is exercised by Nagar Palika, Nainital, whereasfishery of Bhimtal, Naukuchiatal and Sattal is managed by the fisheries department of U.P. The averageper hectare productivity of fish in respect of latter three lakes, taking five years catches into consideration,is low. The resource potential is not less and the productivity can be reasonably enhanced provided bettermanagement practices are undertaken and appropriate technologies are applied. Original fish fauna ofcommercial importance in these upland waters is basically constituted by mahseer and schizothoracids,but the introduction of common carp, Indian major carps, silver carp and grass carp has shown encouragingresults. Nainitallake shows a pollutional status and remedial measures are to be adopted to preventthe recurrent mortality of fish during winter because of oxygen deficiency. All the four lakes that addto the scenic glory of the area in a specific way, are required to be developed from fisheries angle in orderto ensure aVailability of nutritious food to the local people and also to provide a wider range of attraction,especially for angling-tourism.